A Shared Path: Co-occurrence and Clinical Implications of Celiac Disease and Type 1 Diabetes Mellitus - Wojciech Florczak; Joanna Śnieżna; Jakub Dziewic; Karol Dzwonnik; Wiktoria Domino; Urszula Zelik; Gabriela Trestka; Maria Przygoda; Jagienka Włodyka; Kamila Stępień; Sabina Adamczyk (Quality in Sport)
Introduction: